Youth power in precarious times : reimagining civic participation - Brough, Melissa, 1979- (Duke University Press, 2020)
"YOUTH PARTICIPATION IN PRECARIOUS TIMES considers municipal and activist efforts to promote civic participation and technological innovation in Medellín, Colombia, a city known for a history of violence and narcotrafficking, where youth had been experiencing increasing political and economic disenfranchisement. "Participation" has become a mainstream technique of commodification in digital culture, as youth are encouraged to interact with commercialized social media and ad campaigns. But Melissa Brough seeks to distinguish simple digital interactions of this sort from truly engaged political participation, with the potential to reshape public life and relations of power. By following the story of a youth-led hip hop activist collective and other youth-led initiatives, Brough shows how the combination of grassroots tactics and digital technologies can open up space for youth participation in local politics, from participatory budgeting to citizen media. Brough shows that successfully generating youth participation requires ecologies of artistic and grassroots engagement, not simply open digital and media technologies. The book's first chapter demonstrates that cultivating a participatory public culture that values the voices of non-hegemonic groups requires lowering barriers to participation, developing youth skills and capacity to participate, and creating spaces and cultures of participation. The next chapter contrasts two projects, Medellín Digital, an e-government services portal, and Ciudad Comuna, a multimedia communication collective, to show that digital communication can enhance or improve processes of participation only if digital technologies are integrated with attention to their local context. Brough then turns to La Red de Hip Hop La Elite and Son Bataí, an Afro-Colombian youth collective, both youth-run cultural organizations that gained social capital and had to negotiate sometimes conflictual, sometimes collaborative relationships with local governments. Their tactics of reterritorialization-reclaiming public space with dance and graffiti-as well as their reliance on participatory leadership, popular education, mentorship, and support for individual free expression provide a roadmap for successfully promoting a culture of nonviolence and engagement among marginalized youth. Finally, the book turns to Medellín's institutional participatory budgeting process to show how it catalyzed public debate and opened up civil polyculture in a way that effectively empowered marginalized groups"--